-43-3x=6-9x

Simple and best practice solution for -43-3x=6-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -43-3x=6-9x equation:


Simplifying
-43 + -3x = 6 + -9x

Solving
-43 + -3x = 6 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-43 + -3x + 9x = 6 + -9x + 9x

Combine like terms: -3x + 9x = 6x
-43 + 6x = 6 + -9x + 9x

Combine like terms: -9x + 9x = 0
-43 + 6x = 6 + 0
-43 + 6x = 6

Add '43' to each side of the equation.
-43 + 43 + 6x = 6 + 43

Combine like terms: -43 + 43 = 0
0 + 6x = 6 + 43
6x = 6 + 43

Combine like terms: 6 + 43 = 49
6x = 49

Divide each side by '6'.
x = 8.166666667

Simplifying
x = 8.166666667

See similar equations:

| 33.7=9c-5 | | 3e-5=19.9 | | Y-23-37Y=3 | | p-18=18(h-6) | | 5x-14=16x | | p-18=23/3(h-6) | | 1x+34=26 | | 2x^2-12x+68=100 | | p=23/6h+18 | | 0=-4/5x-4 | | 7x+10=3x+78 | | -5t^2+40t+1.2=60 | | 5x+26=125-5x | | 24/34=4y+12/85 | | 45X^2+15X+5=0 | | 7/9=x/108 | | x^7z^5/x^4z | | 1/5u-5/2=-7/3 | | 18(t+4)=9t/9 | | y=-7/8(-7)+7 | | 50=3(5+16)-2(s-2) | | C^2+4b= | | -31*-18+3x=38 | | (7/y+6)=6 | | -7/8w=35 | | -4/3*u=12 | | 5(y-1)=2y+1 | | -3/4*u=12 | | Z-10=-18 | | 12-2x6+2/2=X | | 2+5-3*4/2 | | 2k+3=-17 |

Equations solver categories